ANALISIS STRUKTUR INDUSTRI PEMBIAYAAN INDONESIA - Johan, Suwinto (Jurnal Muara Ilmu Ekonomi dan Bisnis, 2017)
The aim of this paper is to study the structure of the Indonesia Finance Company Industry over the periode 2001-2010. The finance company industry is growing rapidly from Rp37 trillion in 2001 to Rp221 trillion in 2010 with a compounded annual growth rate (CAGR) of 122%. At the same time, the number company in the industry has reduced from 245 in 2001 to 191 in 2010. We use the Concentration Ratio to measure the structure of the industry. Our sample consists of 97 companies in 2001 to 127 companies to 2010. The empirical results show that Indonesia finance company industry is not highly concentrated. In fact, there is a significant increase in the concentration ratio since 2000 to 2010, especially the concentration in Concentration Ratio of 4 largest companies (CR4), Concentration Ratio of 8 largest companies (CR8) and Concentration Ratio of 12 largest companies (CR12). However, there is a potential of higher concentration if we group the companies by the shareholders’ ownership, due to the controlling issue of the shareholders.Keywords : Market Structure, Concentration Ratio, Regulation